Encyclopædia Britannica : micropeadia (Encyclopædia Britannica, 1997)
Contains articles on more than 65,000 subjects covered in articles that range from concise explanations to comprehensive expositions. Includes more than 400,000 references hyperlinked to text articles and more than 10,000 links to images and tables. Also includes a 44 million-word index, the Merriam-Webster's collegiate dictionary (10th ed.), Nations of the world, the Propædia (outline of knowledge), and a copy of Netscape Navigator.